Reposing of Archeological expert system based on Csörsz ditch - Benő, Dávid (Acta Agraria Kaposváriensis, 2011)
Expert systems are originated from the research of the artificial intelligent, drawn conclusion from information stored in knowledgebase and datebase by mathematical logic. In this paper the base of an archeological expert system’s database is reposed a model of Csörsz Ditch. Csörsz Ditch is a buildup in the Carpathian basin, according to our present-day knowledge that was a Roman-Sarmatian fortification system, run through Hungary. Its mean width is 8 m, mean depth 2,5 m, to recently many segments have been ploughed down, but there are some lines with good condition. In this paper it is shown the take-off data, datasources to the build up of the expert system, the building of the geoinformatic system, the structure, and making of the latest expert system.
Keywords: expert system; Csörsz Ditch; geoinformatics